Information, motivation and behavior-based intervention in improving knowledge, attitude and preventive practices related to tuberculosis among HIV patients in Nigeria - Bisallah, Chindo Ibrahim (2017)
The rising incidence of tuberculosis (TB) among HIV patients poses a great threat to TB control in Nigeria. The risk of development of active TB in HIV-infected individuals is up to 20-37 times higher than those that are HIV negative. Out of 87,211 TB cases (including HIV-positive TB) in Nigeria in 2015, 14,846 TB patients were HIV-positive were registered for treatment and care. Poor knowledge of TB amongst people living with HIV is associated with high transmission and delay in healthseeking behavior. The objective of this study was to develop, implement and evaluate the effectiveness of information, motivation and behavior based intervention program in improving knowledge, attitude and preventive practices related to tuberculosis among HIV patients in General Hospital, Minna, Nigeria. A randomized control trial was conducted to determine the effectiveness of a newly developed information, motivation and behavior based intervention program on TB knowledge, attitude and preventive `practices. Respondents were randomized into intervention and control groups. The intervention group received health education intervention regarding tuberculosis using the manual developed. The control group received the normal services provided for the HIV patients by Ministry of Health. Both programs were delivered by trained experienced facilitators. Baseline, immediate post-intervention, three months, six months and nine months assessment was carried out. Mixed design ANOVA was used to determine the effectiveness of the intervention. The study results showed no significant difference in knowledge, attitude and preventive practices regarding tuberculosis between the intervention and control group at baseline (p=0.142, 0.506 and 0.784 respectively). There was a significant change in good knowledge within the intervention group from baseline to immediate postintervention, three, six and nine months follow up (39.8%, p = 0.001, 38.9%, p = 0.001, 40.7%, p = 0.001 and 39.8%, p = 0.001 respectively). There was no significant change in knowledge regarding TB within the control group from baseline to immediate post-intervention, three, six and nine months follow up (-12.4%, p =0.08, 14.1%, p = 0.068, 7.9%, p = 0.298, 6.2%, p = 0.419 respectively). Similarly, there was a significant change in positive attitude and good preventive practices from baseline to immediate post-intervention, three, six and nine months follow up within the intervention group. There was significant main effect for group [F = (1,218) = 665.925, p = 0.001, partial ἠ² = 0.753]; time [F = (3.600, 218) = 52.620, p = 0.001, partial ἠ² = 0.0.194] and the interaction between group and time [F = (3.600, 218) = 34.389, p = 0.001, partial ἠ² = 0.136) for tuberculosis-related knowledge. Likewise, the main effects for group, time and the interaction of group and time for respondent’s attitude and practice regarding tuberculosis were significant. The information, motivation, and behavior based intervention program developed was effective in improving knowledge, attitude and practice regarding tuberculosis among HIV patients. It is highly recommended that a structured information, motivation, and behavior based intervention program regarding tuberculosis targeted at HIV patients be included in the national tuberculosis control guidelines.